Double hit & double expressor lymphomas: a multicenter analysis of survival outcomes with CD19-directed CAR T-cell therapy - Karmali, Reem; Shouse, Geoffrey; Torka, Pallawi; Moyo, Tamara K.; Romancik, Jason; Barta, Stefan K.; Bhansali, Rahul; Cohen, Jonathon B.; Shah, Nirav N.; Zurko, Joanna; Kenkre, Vaishalee P.; Hess, Brian; et al. (Blood cancer journal (New York), 2025)
Double-hit (DHL) and double expressor (DEL) DLBCL have poor prognosis with standard therapy but CART may overcome this poor prognostic impact. In this multicenter retrospective study, we sought to confirm this observation by evaluating survival outcomes among patients with relapsed/refractory DHL and DEL treated with CART and evaluate outcomes of relapse post-CART. A total of 408 adult patients with relapsed/refractory DLBCL from 13 academic centers were included based on the availability of DHL and DEL. All 408 patients were included in the DHL ( n = 80) vs non-DHL ( n = 328) analysis, while 333 patients were included in the analysis of DHL ( n = 80) vs DEL ( n = 74) vs non ( n = 179). On MVA, there were no differences for PFS for DHL vs non-DHL (HR 0.8, 95%CI 0.5–1.3, p = 0.35) or DHL vs DEL vs other (three-way p value, p = 0.5). Response rates and toxicities were similar among groups. Patients with DEL had the highest relapse rates post-CART, while DHL had the worst overall survival after CART relapse. In sum, our data support the notion that CART cell therapy can overcome the poor prognostic impact of DHL and DEL DLBCL in the relapsed/refractory setting. Additionally, patients with DHL that relapse after CART have a very poor prognosis.